2022
DOI: 10.3390/ijerph19074279
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis in Athletes Recovering from COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: To assess the event rates of myocarditis detected by Cardiac Magnetic Resonance (CMR) in athletes who recovered from COVID-19. Methods: A systematic literature search was performed to identify studies reporting abnormal CMR findings in athletes who recovered from COVID-19. Secondary analyses were performed considering increased serum high sensitivity troponin (hs-Tn) levels and electrocardiographic (ECG) and echocardiographic (ECHO) abnormalities. Results: In total, 7988 athletes from 15 studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 56 publications
1
23
1
6
Order By: Relevance
“…In accordance, a study of children who recently recovered from mildly symptomatic COVID-19 infections showed no evidence of myocardial inflammation, fibrosis, or functional cardiac impairment on CMR [ 27 ]. Furthermore, the rate in young athletes was also lower than those previously reported in an older population [ 28 ]. Hence, these results are reassuring, however, do not rule out cardiac involvement in ACHD patients with more severe symptoms of COVID-19 requiring hospitalization or treatment in the intensive care unit.…”
Section: Discussioncontrasting
confidence: 60%
“…In accordance, a study of children who recently recovered from mildly symptomatic COVID-19 infections showed no evidence of myocardial inflammation, fibrosis, or functional cardiac impairment on CMR [ 27 ]. Furthermore, the rate in young athletes was also lower than those previously reported in an older population [ 28 ]. Hence, these results are reassuring, however, do not rule out cardiac involvement in ACHD patients with more severe symptoms of COVID-19 requiring hospitalization or treatment in the intensive care unit.…”
Section: Discussioncontrasting
confidence: 60%
“…Conflicting results have been reported over the last months regarding the prevalence of CMR findings (from 0.4 up to 15%) suggestive for myocardial involvement in competitive athletes during the recovery after even an asymptomatic or mildly symptomatic SARS-CoV-2 infection [ 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. A recent metanalysis estimated a pooled prevalence of COVID-19-related myocarditis among athletes, ranging from 1 to 4% [ 25 ]. However, given the cross-sectional nature of the previous study designs, with different times of evaluation and protocol applied, and different criteria for recruiting athlete cohorts, uncertainty still exists regarding how to advise a safe return-to-play in competitive athletes.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple factors might have contributed to our findings. First, the majority of adverse events occurred in the arrhythmic group, which is already known for being associated with worse outcomes [ 6 , 7 , 25 ]. Second, a non-trivial subset of patients with abnormal EST (7 of 35, 20%) received a diagnosis of active myocarditis following the subsequent disease restaging: this observation suggests that adverse prognostic significance may be carried out by active myocardial inflammation, as previously reported [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, international guideline documents agree in recommending the use of EST after six months from acute myocarditis before resuming competitive sport participation [ 4 , 5 ]. In this setting, the absence of arrhythmia and ischemia signs is needed to demonstrate safety during incremental physical activity [ 6 ]. Remarkably, the evidence currently supporting the role of EST in myocarditis focuses on the classic acute coronary syndrome (ACS)-like presentation of myocarditis, which is the most common and benign scenario [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%